Effect of Allicin for Re-epithelialization During Healing in Oral Ulcer Model - Renny Ayu Novianty; Bernadetta Esty Chrismawaty; Goeno Subagyo (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2011)
Allicin (diallyl thiosulfinate) is the main component of fresh garlic with multi-bioactivities as therapeutic agent. Recently, allicin is being proposed as alternative therapy for aphthous ulcer. The purpose of this study was to determine the effect of topical allicin in aqueous garlic extract on re-epithelialization during healing of acetic acid induced oral ulcer model. Thirty males SD rats aged 2 months were equally divided into two groups as experimental and control groups. After sedated with 0.2 ml intramuscular Ketamine injection, ulcer model was made by applying 99.5% glacial acetic acid-moistened paper disc on rat buccal mucosa. This would gene- rate an immediate necrotic tissue, which produced a single crateriform ulcer in each of the experimental rats for the next two days. In the experimental group, one drop of allicin was applied twice daily onto the lesion. Three rats in each group were sacrificed on days 2, 3, 6, 9 and 12 after induction and were recorded as H0, H1, H4,H7 dan H10 groups, respectively. The tissue samples from buccal mucosa were processed for HematoxylinEosin (HE) staining, and then evaluated histologically. Re-epithelialization was assessed by measuring the thickness of the epithelium using an ocular micrometer under a light microscope. Data were analyzed statistically by Independent t-test with significant p-values of <0.05 (95%). Based on histological findings and trend graphs, it can be concluded that the topical application of allicin can accelerate re-epithelialization of ulcer healing process. This study suggests that allicin in aqueous garlic extract could be developed as therapeuticagent for aphthous ulcer